Comparison of force-balance and pressure measurements on deck strips on a stationary bridge model. Issue 164 (May 2017) - Yan, Lei; Zhu, Le Dong; Flay, Richard G.J.
Abstract: Synchronical measurements of fluctuating lifts and moments on six bridge deck strips in a motionless 1:45 scale model were carried out in the TJ-2 Wind Tunnel at Tongji University by using six miniature force-balances. Furthermore, synchronical measurements of pressures on six same-arranged strips in another identical model were also conducted for comparison. The paper describes how the new balance functioned and measured the fluctuating lift and moments, and compared the results with those from the pressure measurements. The comparisons demonstrate that the shapes of the spectra, and standard deviations of the lift and moment coefficients from the pressure and force-balance measurements show very good agreement, and the span-wise coherences and aerodynamic admittances of lift and moment are also very similar. The innovative miniature force-balance attached to the thin deck strips was proven to work reliably and accurately, and it had many advantages compared to pressure measurements, especially for bridge decks with wind barriers, crash barriers and other ancillaries, on which the wind loads would not be measured in pressure measurement tests. It was found that the ancillaries of bridge have little effect on the span-wise coherence of the buffeting force, but have a strong influence on the aerodynamic admittance. Highlights: Innovative miniature balances attached to thin deck strips work reliably and accurately. Ancillaries of bridge have little effect on the span-wise coherence of the buffeting force. Ancillaries of bridge have a strong influence on the aerodynamic admittance.